Use of serum-free media for peripheral blood mononuclear cell culture and the impact on T and B cell readouts - Cochrane, Stella; Saib, Ouarda; Sheffield, David (Frontiers in Toxicology, 2024)
IntroductionAs part of a wider programme of work developing next-generation risk assessment approaches (NGRA) using non-animal methods (NAMs) for safety assessment of materials, Unilever SEAC is exploring the use of a peripheral blood mononuclear cell (PBMC) system to investigate how cells from different arms of the human immune system are impacted by different treatments. To maximise human relevance, the cell cultures are supported by human serum, but this came with some challenges, including an inability to measure induced levels of immunoglobulins due to high background levels. Therefore, a study comparing use of human sera containing media with three different chemically defined serum-free media was undertaken.Materials and MethodsPBMC were isolated from healthy donors and cultured in the absence (media alone) or presence of stimulation reagents (CpG-ODN plus IL-15, Pokeweed Mitogen (PWM) or Cytostim (CS)), in RPMI plus human serum, AIM-V, CTS OpTmizer T cell expansion SFM or X-VIVO 15 media. T cell (CD4+ and CD8+) and B cell proliferation and viability were measured after 6 days, along with levels of total IgG in the cell culture supernatants.ResultsEach of the serum-free media tested supported good levels of viable and proliferating T cells and B cells over the 6 days of culture, with only a few, small differences across the media, when there was no stimulation. They also enabled detection of a stimulation-evoked increase in IgG levels. There were however some differences in the viability and proliferation responses of T and B cells, to different stimuli, across the different media.DiscussionThe serum-free media formulations tested in this study offer defined systems for. measuring B cell IgG responses, in vitro, in either a ‘T cell-independent’ (CpG + IL-15) or “T cell-dependent” (PWM or CS) manner and for assessing B cell proliferation, particularly in response to a “T cell-independent” stimulus. However, there are some characteristics and features endowed by human serum that appear to be missing. Therefore, further work is required to optimise animal-free, chemically defined culture conditions for PBMC based assays for inclusion in tiered safety assessments.